STRATEGIES OF REQUEST IN “THE HUSTLE” MOVIE - Safitri, Ajeng Resva; Ambalegin, Ambalegin (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
This research found out the strategies of request in utterances. The Hustle movie was used as data source of this research. Data of this descriptive qualitative research were utterances of request in the movie. The researchers used observational method and non-participatory technique. The researchers collected data watching and listening to utterances in the movie. The data were analyzed by using pragmatic identity method and pragmatic competence- in equalizing technique. The data were analyzed by using theory from Blum-kulka & Olshtain (1984). Results showed that request strategies had 59 data.  Mood derivable consisted of 21 data, explicit performatives consisted of 9 data, hedged performative consisted of 4 data, locution derivable consisted of 5 data, language specific suggester formula consisted of 6 data, reference to prepatory conditions consisted of 7 data, mild hints consisted of 3, scope stating consisted of 1 data and strong hints consisted of 3 data. From all strategies, mood derivable was the most common strategy. The characters used this strategy because the characters were already familiar to one another and the situation made the characters request the others in a direct way.